Social contexts and black families’ engagement in early childhood programs - Jane Leer; Imari Z. Smith; Zoelene Hill; Lisa A. Gennetian (PLoS ONE, 2025)
In the U.S., the federal government and dozens of cities have invested in home visiting programs intended to be universally available at scale to support caregivers of young children. Evaluations find that participation in these programs reduces maternal mortality, improves maternal mental health, and supports children’s healthy development. Yet, many parents of young children who are invited to participate in home visiting programs do not enroll. This study fills gaps in the literature by examining how the broader social context affects Black families’ engagement in home visiting programs. Via focus groups, survey data from a socioeconomically diverse sample of Black parents across the U.S., and a pre-registered field experiment, we capture views of and experiences with early childhood home visiting programs. We assess the responsiveness of these views to the broader social context and examine implications for interest and participation in home visiting programs. Focus group participants described benefits of home visiting while also expressing concerns about being unfairly judged about their parenting practices and the risk of a home visit resulting in child welfare system involvement. One out of four Black parents surveyed associated the term “home visit” with surveillance (i.e., government scrutiny of parenting), and associating “home visit” with surveillance was empirically correlated with lower participation in home visiting programs. Further, our pre-registered survey experiment showed a causal link between surveillance fears and home visit engagement. Reading a news article about a family’s experience with the child welfare system decreased interest in home visiting among Black parents, while labeling a program as “new baby wellness” rather than “home visit” increased interest. Collectively, the findings point to ways in which the broader social context of parenting/parental surveillance negatively affects Black parents’ participation in early childhood home visiting programs despite their interest.